2014
DOI: 10.1302/0301-620x.96b4.33210
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous vertebral and posterior communicating arteries as a risk factor in instrumentation of the posterior cervical spine

Abstract: We investigated the incidence of anomalies in the vertebral arteries and Circle of Willis with three-dimensional CT angiography in 55 consecutive patients who had undergone an instrumented posterior fusion of the cervical spine. We recorded any peri-operative and post-operative complications. The frequency of congenital anomalies was 30.9%, abnormal vertebral artery blood flow was 58.2% and vertebral artery dominance 40%. The posterior communicating artery was occluded on one side in 41.8% of patients and bila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
(26 reference statements)
0
4
0
1
Order By: Relevance
“…In Serbia, Ješić et al [19] discovered A1 aplasia in 2.9% of the angiograms of 1000 patients with different pathology; however we found 0.51% of (unilateral and bilateral) ACA aplasia in cadavers autopsied due to different reasons and pathology as well. In Japan, Wanibuchi et al [54] discovered 11.1% of A1 aplasia among nine patients with the ACA aneurysms, whereas Uchino et al [47] recorded 50/891 (5.6%) the patients with A1 aplasia suspected to suffer from cerebrovascular disease, while Nagahama et al [34] recorded 3.6% of A1 aplasia among the 55 patients hospitalized because of the instrumentation of the posterior cervical spine. In addition, Uchino et al [47] found a higher frequency of aplasia of the right ACA (31) vs. the left ACA (19) aplasia in Japanese population.…”
Section: Discussionmentioning
confidence: 99%
“…In Serbia, Ješić et al [19] discovered A1 aplasia in 2.9% of the angiograms of 1000 patients with different pathology; however we found 0.51% of (unilateral and bilateral) ACA aplasia in cadavers autopsied due to different reasons and pathology as well. In Japan, Wanibuchi et al [54] discovered 11.1% of A1 aplasia among nine patients with the ACA aneurysms, whereas Uchino et al [47] recorded 50/891 (5.6%) the patients with A1 aplasia suspected to suffer from cerebrovascular disease, while Nagahama et al [34] recorded 3.6% of A1 aplasia among the 55 patients hospitalized because of the instrumentation of the posterior cervical spine. In addition, Uchino et al [47] found a higher frequency of aplasia of the right ACA (31) vs. the left ACA (19) aplasia in Japanese population.…”
Section: Discussionmentioning
confidence: 99%
“…During anterior corpectomy, excessive lateral body resection is a risk factor for the integrity of the vertebral artery [32], and a duplication or triplication of the foramen, with or without a multiple artery lumen, could disorientate the surgeon. In posterior procedures, such as lateral mass and pedicle screw fixation, there is also a risk of injury [32,33]. An aberrant course of the artery may cause an arterial injury during the screw placement and this may be clinically important if the contralateral artery is hypoplastic (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] These cases will result in brain-stem infarction that can be fatal if the vertebral artery is occluded. Therefore, it should be considered that reflow of the vertebral artery has great benefit, and it should not be considered that no issues will occur, although the screws perforated only because the vertebral artery is already occluded.…”
Section: Discussionmentioning
confidence: 99%